Does trust associate with political regime? - Sára Khayouti; Hubert János Kiss; Dániel Horn (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2020)
Since trust correlates with economic development and in turn economic development associates with political regime, we conjecture that there may be a relationship between trust and political regime. We investigate if trust aggregated on the country level correlates with the political regime. We do not find any significant association, with or without taking into account other factors (e.g. regional location, economic development, geographic conditions, culture) as well.
Keywords: D02; D12; 330; political regime; trust